Law Enforcement against Traffic Accident - Rio Tumiyadi Maulana; Sri Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
The purpose of this study is as follows: To determine and analyze the factors that cause traffic accidents. To find out and analyze law enforcement against traffic accidents. To find out and analyze barriers in traffic accident law enforcement and their solutions. The approach used by the author to discuss the above problems is to use a sociological juridical approach, namely approaching the problem through legal research by looking at the legal norms that apply in society. The research specification used in this research is descriptive analytical. Based on the results of this study, the factors that cause traffic accidents include: the driver / driver is sleepy, the factor of the vehicle itself, road factors, environmental factors. Law enforcement against traffic accidents can be carried out by applying the provisions of Act No. 22 of 2009 concerning road traffic and transportation Article 310 if it concerns handling traffic accidents for negligence of drivers, either resulting in death or only injury. Obstacles in law enforcement of traffic accidents is the participation of the community, police officers, local governments at level I and level II as well as the role of the central government to work together to create a safe, comfortable and peaceful environment for the community. Efforts to overcome obstacles in traffic accident law enforcement are as follows: (a). Making efforts on the Government's side to revise the Articles in Act No. 22 of 2009 concerning road traffic and transportation; (b). Increase the number of personnel for the realization of maximum service; (c). Doing morning apples on roads that are at the heart of traffic problems; and D). Fostering legal awareness of the community to obey the law in traffic.